Music, Drinking and Dance at Aristocratic Russian Weddings under Peter the First as Witnessed by Friedrich Wilhelm von Bergholz - Sander, Elizabeth (Intersections, 2005)
Dance and related rituals as practised at aristocratic wedding ceremonies in Russia at the end of the reign of Peter I ("the Great," 1672-1725) are examined in this article. The central source employed in this research is a diary written in Russia by the Holstein nobleman Friedrich Wilhelm von Bergholz (1699-1765) between 1721 and 1725. Dancing on the first day of the aristocratic Petrine wedding ceremony was evidently governed by a stable formal plan consisting of formal reverences, ceremonial dancing and free dancing. Minuets, as well as dances identified as Polish and English, were danced.